RESEARCH ON THE INFLUENCE OF CHINESE URBAN RESIDENTS’ CONSUMPTION MOTIVATION ON SPORTS CONSUMPTION BEHAVIOR - LI, JIAYI (Journal of Buddhist Education and Research (JBER), 2023)
With the vigorous development of China’s economy and sports industry, Chinese urban residents’ participation-based sports consumption behavior has undergone tremendous changes. This thesis focuses on the transformation of urban residents’ sports lifestyle, takes the sports consumption motivation of urban residents as the breakthrough point to study its influence on sports consumption behavior, and analyzes the transformation process of urban residents’ sports lifestyle. Through empirical analysis, it is concluded that consumer motivation has a positive impact on sports consumption behavior, and reasonable suggestions are put forward.